Novel method and tool to identify solitary waves in the Martian plasma environment - Pandey, Sahil; Kakad, Amar; Kakad, Bharati (Frontiers in Astronomy and Space Sciences, 2025)
This paper introduces a method and an innovative graphical user interface (GUI) tool to identify bipolar solitary wave structures in the Mars Atmosphere and Volatile EvolutioN (MAVEN) mission dataset. As input to this tool, we utilized medium-frequency burst mode calibrated electric field data obtained from the Langmuir Probe and Waves (LPW) instrument aboard MAVEN. To detect solitary waves, we first discuss the typical theoretical solitary wave structure and its key features. Based on these features, we developed a series of mathematical conditions that are applied to the LPW electric field dataset. After rigorous testing, a MATLAB executable GUI application named SWIT (Solitary Wave Identifying Tool) was developed. The output of SWIT provides the amplitude, width, and time of occurrence of the solitary waves. Furthermore, we evaluate the accuracy and limitations of SWIT. It is found that SWIT demonstrates high efficiency. It is a dedicated identifier for analyzing medium-frequency electric field measurements from the MAVEN spacecraft to search for solitary wave structures in the Martian plasma environment. It is suggested that this novel method can be applied to datasets from different spacecraft in other planetary plasma environments with minor modifications.